Selenium-Catalyzed Trifluoromethylsulfinylation/Rearrangement of Allylic and Propargylic Alcohols: Access to Allylic and Allenic Triflones - Zhu, Deng; Luo, Hui-Yun; Chen, Zhi-Min (Organic letters, 2021)
A selenium-catalyzed trifluoromethylsulfinylation/rearrangement of allylic and propargylic alcohols for synthesizing triflones was developed for the first time. Various allylic and allenic triflones were delivered in moderate to excellent yields. After numerous control experiments were performed, it was suggested that this transformation includes an unusual [+SCF3] group disproportionation process that forms [+SOCF3] that is in-situ-catalyzed by selenium, and H2O was used as an oxygen source. This reaction features mild reaction conditions and good compatibility of substrates, and it is transition-metal-free.